Historical roots of the theory of geographical interpretation of the events of history in Islamic thought - Ghofran Barto Shakheetr, Res.; Aqil Abdullah Yassin, Prof.Dr. (lark, 2023)
The philosophy of history holds a significant position among the branches of philosophy as it pertains to the examination of history from a philosophical standpoint. Consequently, numerous theories have emerged to elucidate historical events, among them the Geographic Interpretation Theory, which finds resonance among certain Muslim intellectuals. This signifies the extent of Muslim intellectuals' engagement in the realm of philosophy of history, substantiated by the theory's influence and its alignment with lived experiences, as well as its impact on the past and its implications for the future.
Keywords: Philosophy of history, the course of the movement of history, geographical interpretation